Nurse mentors' experience with local curricula for nursing students - Christiansen, Bjørg; Blomberg, Karin; Lindeflaten, Katrin; Holm Larsen, Monica; Averlid, Gertrud; Salinas, Deborah; Hessevaagbakke, Elisabeth (Nordisk Tidsskrift for Helseforskning, 2023)
Several studies have shown that nurse mentors experience the education's learning outcomes as generally defined. An R&D-related collaborative project was therefore launched. Part 1 involved the development of a local curriculum in collaboration with nurse mentors. Part 2 involved a systematic evaluation study focusing on the use of local curricula.The aim was to investigate the importance of local curricula as a tool for clarifying learning outcomes in clinical studies. The study is qualitative with an exploratory and descriptive design based on four focus group interviews with nurse mentors from different levels of the bachelor's education. The analysis process was based on thematic analysis. The findings were: Varying experiences with implementation of local curriculumClarify current learning situationsVarying use in assessment situationsThe nurse mentors experienced the description of learning situations as relevant and recognizable. The local curricula was a good tool in the process assessment of the students.
Keywords: Clinical practice; nurse mentor; local curriculum; learning outcomes; assessment